(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the effect of traditional games (hadang and benteng-bentengan) on improving agility in fourth-grade students at Elementary School 76 Muaro Jambi. This research employed an experimental method with a "One Group Pretest-Posttest Design". The population consisted of all fourth-grade students at Elementary School 76 Muaro Jambi, totalling 60 students. The sample was selected using a purposive sampling technique, specifically male students from class IV A, totalling 14 students. The research instrument used the Illinois Agility Run test to measure students’ agility. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, and hypothesis testing with a t-test using SPSS version 27. The research results showed that traditional games, hadang and benteng-bentengan, proved effective in improving students’ agility. There was a decrease in average completion time from 19.37 seconds in the pre-test to 16.61 seconds in the post-test, indicating an agility improvement of 2.76 seconds. The hypothesis test results showed a significance value of 0.001 (< 0.05), meaning there was a significant difference between students’ agility before and after being given traditional games treatment. Traditional games provide dual benefits: improving students’ physical abilities and helping preserve local cultural heritage. This research proves that learning approaches combining traditional cultural elements with physical development goals can provide optimal results in elementary school physical education.